Numerical modeling of coherent structures during admixture propagation in atmospheric boundary layer over forest canopy - Gavrilov, Konstantin Alexeevich; Morvan, Dominique; Accary, Gilbert; Lyubimov, Dmitry Victorovich; Meradji, Sofiane; Bessonov, Oleg Arkad'evich (Computational Continuum Mechanics, 2010)
The problem is studied using 3D large eddy simulation carried out for a homogeneous canopy. The development of Kelvin-Helmholtz instability over canopy leads to the coherent structures formation observed in the computations. The statistical flow characteristics are captured by the simulations, and the computational results are compared with experiments. The process of passive admixture transport from a forest canopy into a pure atmosphere is studied for two cases, i.e., when the coupled concentration in the forest canopy is constant and variable.